Amine-passivated ZnO electron transport layer for thermal stability-enhanced perovskite solar cells. (1st July 2020) - Yang, Zilu; Fan, Qin; Shen, Tao; Jin, Junjun; Deng, Wenqiu; Xin, Juan; Huang, Xiulin; Wang, Xianbao; Li, Jinhua
Highlights: Perovskite films are deposited on ZnO ETLs by one-step spin-coating. The modification of the amino compounds reduces the contact resistance of the ZnO and improves the quality of MAPbI3 films. The optimal device based on isobutylamine (IBA) modification shows high power conversion efficiency of 18.84%. Abstract: n-Type zinc oxide (ZnO) has high electron mobility, good light transmittance, and a suitable work function and is considered to be a suitable electron transport material in perovskite solar cells (PSCs). However, the chemical compatibility between ZnO and perovskites is poor, making it difficult to prepare highly efficient and stable PSCs by a one-step spin coating method. Here, the ZnO surface is modified with three amino compounds, butylamine (BA), isobutylamine (IBA) and 2-amino-2-methyl-1-propanol (AMP). Three amino compounds can react with 3D perovskite to form a thin and more stable perovskite with a 2D structure, which can improve the stability of ZnO-based PSCs fabricated by one-step method. Interestingly, the conductivity of amine-modified ZnO is also improved due to the presence of amino (NH2 ) and hydroxyl (OH) groups which can induce the dipole polarization. The modification of amino compounds on the surface of ZnO can affect the hydrophilicity of ZnO surface that is related to the crystallization of perovskite film. Devices with IBA modification exhibit improved stability, and the power conversion efficiency (PCE) can reach 18.84%. Therefore, we provide a new strategy to improve the surface of the ZnO electron transport layer for high-performance PSCs fabricated by a one-step method.